Shalawatan as the Head Election Campaign Website for Region Karangpoh Village, Menganti, Gresik - Adinda Dwi Fitriyanti; Nirmala Anggur Aulia (Journal of Religion, Local Politics, and Law, 2025)
Shalawatan is an online activity intended to give thanks to the Prophet Muhammad (peace and blessings be upon him). These activities have become an icon among muslims, especially you who have been carrying out prayer activities. 2024 Gresik County Chief Election. Yesterday was a very intense rivalry between candidate number one and the box. Empty. The competition is fierce because it is triggered by issues related to prospective couples, Number 1. This sparked a campaign by candidate number one's couples, who performed prayers and other activities in the Karangpoh Village Box. This research aims to explore aspects that influence the campaign and the motives of prospective couples' success teams with a caretaker in DSN. Karangpoh Box. The method employed in this research is an insightful observational approach and in-depth interviews. The study was supported. With the theory of social capital proposed by Pierre Bourdieu and subsequently developed by James Coleman (1988) and Robert Putnam (1993), focusing on its impact on Social and economic life. The phenomenon does not seem to affect society. The karangpoh can be seen by the number of votes that the prospective couple number 1 gets. It's less than an empty box.